Pengaruh facilitating conditions, social influences, perceived ease of use, dan perceived usefulness terhadap niat pengguna layanan telemedicine - Ongko, Iren; Tan, Pauline H. Pattyranie (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The presence of telemedicine plays a vital role in the health care system in developing countries, because it can facilitate access to health services, especially in remote areas. However, various factors can influence the acceptance and intention to use a new technology. The purpose of this study is to analyze the factors influencing intention to use telemedicine applications in Indonesia using the Extended Technological Acceptance Model (TAM). The variables studied included facilitating conditions, social influence, perceived ease of use, and perceived usefulness and their influence on behavioral intention variables. This research was conducted using a quantitative approach using online Google Forms questionnaire with 5-point Likert scales. Questionnaires were distributed via social media during November 2022. A non-probability method with convenience sampling technique was employed. A total of 188 respondents were included, and the data collected were analyzed using a multivariate technique using Partial Least Square-Structural Equation Modeling (PLS-SEM). Evaluation of the outer model based on the outer loading (above 0.708), composite reliability and Cronbach’s alpha value (above 0.7) had shown the constructs to be reliable. The AVE value (above 0,50) and discriminant validity test using Fornell-Larcker criterion had shown the constructs to be valid. The results showed that the four independent variables studied had positive influences on the intention to use telemedicine applications.